1990
DOI: 10.1002/net.3230200504
|View full text |Cite
|
Sign up to set email alerts
|

Identifying independence in bayesian networks

Abstract: An important feature of Bayesian networks is that they facilitate explicit encoding of information about independencies in the domain, information that is indispensable for efficient inferencing. This article characterizes all independence assertions that logically follow from the topology of a network and develops a linear time algorithm that identifies these assertions. The algorithm's correctness is based on the soundness of a graphical criterion, called d-separation, and its optimality stems from the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
275
0
4

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(279 citation statements)
references
References 15 publications
0
275
0
4
Order By: Relevance
“…It can be shown that if sets of variables X and Z are d-separated by Y in a directed acyclic graph G, then X is independent of Z conditional on Y in every distribution compatible with G [24,52]. It is precisely this property that will be exploited in the algorithm of Cheng to learn the Bayesian network structure.…”
Section: General Bayesian Network Classifiersmentioning
confidence: 99%
“…It can be shown that if sets of variables X and Z are d-separated by Y in a directed acyclic graph G, then X is independent of Z conditional on Y in every distribution compatible with G [24,52]. It is precisely this property that will be exploited in the algorithm of Cheng to learn the Bayesian network structure.…”
Section: General Bayesian Network Classifiersmentioning
confidence: 99%
“…In the case of a directed acyclic graph they can be read from the graph using a graph theoretic criterion called d-separation [35,24]. What is to be understood by conditional independence depends on the uncertainty calculus the graphical model is based on.…”
Section: Graphical Modelsmentioning
confidence: 99%
“…A causal directed acyclic graph defined by nonparametric structural equations satisfies the global Markov property as stated above (cf. Verma & Pearl, 1988;Geiger et al, 1990;Lauritzen et al, 1990;Pearl, 2000). We will say that (V 1 , .…”
Section: Causal Directed Acyclic Graphs and Signed Edgesmentioning
confidence: 99%